Kedudukan Hukum Harta Waris Sebagai Objek Jaminan Hak Tanggungan Dalam Kewarisan Islam - Yossiramah Sucia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to find out, understand and analyze how the background of the occurrence of collateral for the inheritance which is the object of the mortgage guarantee auction, the process of raising liabilities on the inheritance that are used to make loans for debt repayments and legal positions that are used as collateral for liabilities according to the Islamic heritage. The issue is focused on the legal status of the inheritance, which guarantees the rights and completion of each heir. This problem uses the theoretical referencing of the mertokusumo theory as the theory of legal certainty. The data collected through library research methods are juridical normative and analyzed qualitatively. The results of the study indicate that the inheritance that becomes the mortgage remains a guarantee for repayment by the bank, the bank has the right to execute the collateral which cannot be contested. Execution is carried out on a court decision. The legal position of inheritance according to Islamic inheritance concerning the rights of each heir is the debtor as one of the heirs to settle in deliberation and kinship while still giving the rights of each heir based on Islamic inheritance which has been regulated in the Al-Qur'an Surat Annisa’: 11 the concept of the amount of distribution of inheritance in the Qur'an has regulated proportionally the rights of each heir in the distribution of inheritance. Islam has regulated the balance of rights and obligations for each child fairly.